Modelling of Air Movements in Rooms - Nevrala, D. J. (Cranfield University, 1979)
The assessment of room air movements, in all but elementary cases, relies on investigations using either full-size mock-ups or scaled models. Temperature considerations severly limit the maximum geometric scale factor. A solution is offered by which accurate predictions of the air flows in full-size air-conditioned rooms may be obtained from observations. made with small models if certain criteria are satisfied. The maximum geometric scale-factor can be increased to 8.5, while limiting the maximum working temperature in the model to 100°C, by replacing the convective currents with wall jets of a similar velocity profile, volume flow, momentumfl ux and heat content. A further improvement may be achieved if the scale-factor adopted for the jet nozzle is smaller than the geometric scale-factor. This approach can lead to scale-factors exceeding 11.8. Theoretical studies have shown the replacement of convective currents by plane jets is feasible. In the course of the study, detailed investigations of areas important for the aimsof the project but where there is a dearth of relevant information, were undertaken. To test the validity of predictions and to establish necessary empirical factors, a range of measurements of convective currents and their replacement jets were'carried out. The results showed that a virtual identity of maximump rofile velocity, momentumfl ux and volume flow at the replacement cross-section could be achieved. Based on measured empirical factors, a simple procedure, valid for the majority of practical applications, by which replacement jets can be calculated directly from convective surface parameters is given. Thus, the aim of this study, namely the worthwhile use of a small model which can be constructed cheaply, has been achieved.